Persistent docetaxel-induced supravenous erythematous eruption - Karina de Almeida Pinto Fernandes; Paulo Antônio Oldani Felix (Sociedade Brasileira de Dermatologia, 2015)
AbstractTaxanes are drugs used to treat many types of cancer, including breast and lung cancer. The most common side effects of these drugs are neutropenia and mucositis. Signs of skin toxicity are observed in about 65% of cases and include alopecia, hypersensitivity reactions, persistent supravenous erythematous eruption, nail changes, scleroderma reactions and others. We report two cases of skin reaction to docetaxel and warn that it is not necessary to interrupt the treatment in these cases.